A new genus and species of Malvapiini (Coleoptera: Curculionoidea: Apionidae) from Ghana MIŁOSZ A. MAZUR (Poland) - Mazur, Miłosz A. (Zootaxa, 2011)
Anacrapion wanati, a new genus and species of Malvapiini is described from Ghana (West Africa). Apion (Catapion) ghanense Voss, 1973 and Apion (Pseudapion) lamottei Hoffmann, 1963 are transferred to the new genus. A key to species of Anacrapion, and to the genera of Malvapiini is provided.